Meta-analysis to determine the effect of energy additives on the pH of tropical forage silages - Torres, Mildrey; Herrera, Magaly; Rodriguez, R. (Cuban Journal of Agricultural Science, 2021)
A meta-analysis was developed to estimate the effect of energy additives on the pH of tropical forage silages. A total of 197 studies were reviewed, located in the databases EBSCO, Scielo, ScienceDirect, ResearchGate and the Cuban Journal of Agricultural Science. The selection of the articles took into account the fulfillment of the inclusion criteria, the reliability of the search and the evaluation of the methodological quality of each study. The difference in standardized means between the treated sample with the additive and the control was defined as the effect size index with its respective 95% confidence interval. The Cochrane Q test was used as a heterogeneity test, and the inconsistency statistic was used to quantify the variability percentage of the results between studies. The subgroup analysis technique was applied for the analysis of qualitative moderating variables and metaregression for quantitative variables. Using a random effects model, the results showed the global effectiveness of the energy additives evaluated d (pH) = 3.077 (C.I 95 % (2.365–3.789)). Despite the high variability found in the literature that was consulted (I2> 75 %), the meta-analysis techniques confirmed in a non-experimental way the favorable effect of using energy additives to benefit the fermentation process of the silage and its conservation. In this study, the description of each step of the methodology can be use as a guide to extrapolate and apply the meta-analysis to other spheres from the agricultural sector. Key words: fermentative indicator, forage conservation, heterogeneity, subgroup analysis, meta-regression